Analysis of readmissions data among frail and non-frail patients presenting for acoustic neuroma. (May 2022) - Nasrollahi, Tasha S.; Shahrestani, Shane; Borrelli, Michela; Raskin, Jonathan; Hopp, Martin L.; Wu, Arthur W.; Miller, Mia E.; Wong, Yu-Tung
Highlights: Current research for resection of acoustic neuroma considers age rather than frailty. Frailty is tied to a person's dependency and not a necessary consequence of aging. Frailty is more predictive of postoperative outcomes when compared to age alone. Abstract: The incidence of acoustic neuromas in the United States is 1.09 per 100, 000 with 23, 739 newly diagnosed cases in the years 2004 to 2010. Because the recent literature has supported that frailty can serve as a more accurate predictor of patient outcomes when evaluated with age, and is an important variable to consider in the course of patient treatment. The objective of this study was to compare the outcomes of frail patients who had undergone surgery for acoustic neuroma with their non-frail counterparts. The authors conducted a retrospective cohort study of geriatric patients receiving cranial neurosurgery for acoustic neuroma between 2016 and 2017 by using the Nationwide Readmission Database. A total of 396 frail patients and 402 non-frail patients were identified through the database of undergoing surgery for acoustic neuroma. Frail patients had statistically higher rates of readmission (p < 0.01), post-operative infection (p < 0.01), facial paralysis (p < 0.01), urinary tract infection (p < 0.01), hydrocephalus (p < 0.01), and dysphagia (p < 0.01). These post-op morbidities likely led to the increased length of stay (p < 0.01), non-routine discharge (p < 0.01), and all payer cost seen in frail patients (p < 0.01). However, no significant difference was found between frail and non-frail patients with regards to CSF leak, post hemorrhagic anemia, myocardial infarction, and mortality. Patient frailty status is a significant predictor of poor outcomes in the postoperative sequelae of acoustic neuroma surgery. Further, models including patient frailty plus age outperformed those using age alone for prediction of several postoperative complications.